1998
DOI: 10.1111/j.1440-1681.1998.tb02281.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Thioctic Acid in Rodent Models of Insulin Resistance and Diabetes

Abstract: 1. The antioxidant thioctic acid (TA) has been used in the treatment of diabetic neuropathy and recent studies have suggested that TA also has pancreatic and peripheral effects that improve glucose transport and metabolism. In the present study, the metabolic effects of TA were evaluated in rodent models of insulin resistance (fructose-fed Sprague-Dawley rat) and insulin deficiency (streptozotocin (STZ)-induced diabetic rat). Oral and intravenous glucose tolerance tests (OGTT and IVGTT, respectively) were perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Increasing evidence obtained from both experimental studies and investigations in insulin-resistant individuals supports the notion that thioctic acid exerts a beneficial effect on insulin-regulated glucose disposal and may be considered as a new antidiabetic agent 18,19]. However, recently the peripheral effects of thioctic acid on glucose metabolism have been questioned [20]. By using a primary muscle cell with a very high sensitivity towards insulin [9-11], we have now provided additional evidence that thioctic acid is able to completely mimic insulin action on the glucose transport system.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence obtained from both experimental studies and investigations in insulin-resistant individuals supports the notion that thioctic acid exerts a beneficial effect on insulin-regulated glucose disposal and may be considered as a new antidiabetic agent 18,19]. However, recently the peripheral effects of thioctic acid on glucose metabolism have been questioned [20]. By using a primary muscle cell with a very high sensitivity towards insulin [9-11], we have now provided additional evidence that thioctic acid is able to completely mimic insulin action on the glucose transport system.…”
Section: Discussionmentioning
confidence: 99%
“…According to the information in Table 1, administration of different doses of α‐LA (50 and100 mg/kg, 4–12 weeks) to alloxan‐induced diabetic rats decreased lipid profile and blood glucose (Banji et al, 2011; Thaakur & Lakshmi, 2008). Also, it was observed that administration of α‐LA (10 and 50 mg/kg, 5–10 days) to STZ‐induced diabetic rats decreased fasting blood glucose and exhibited antidiabetic effects (Black et al, 1998; Khamaisi et al, 1999). In another study, oral administration of α‐LA 100 mg/kg for 8 weeks to STZ‐induced diabetes rats reduced HbA1c levels and blood glucose (Budin et al, 2007).…”
Section: In Vivo Studiesmentioning
confidence: 99%
“…), fructose‐fed (Black et al. ), streptozotocin‐induced diabetic rats (Nagamatsu et al. ; Black et al.…”
Section: Introductionmentioning
confidence: 99%